2011
DOI: 10.1080/1745039x.2011.594345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of complementary effects of 9,10-anthraquinone and fumaric acid on methanogenesis and ruminal fermentationin vitro

Abstract: The objective of the present study was to investigate the hypothesis that 9,10-anthraquinone (AQ) in combination with fumaric acid (FMA) may provide complementary effects to inhibit methanogens and enhance rumen's capacity for better utilisation of FMA towards propionate production. Three levels of AQ and four levels of FMA were tested in a 3 x 4 factorial design using in vitro gas production technique. AQ reduced the total gas and methane production significantly. The combination of 4 ppm AQ with FMA had addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
1
5
0
2
Order By: Relevance
“…Tatsuoka et al ( 2008 ) and Ebrahimi et al ( 2011 ) could decrease H 2 accumulation in methanogenesis-inhibited ruminal batch cultures by adding fumarate or malate. Whilst the addition of a substrate or a fermentation intermediate might remove or decrease the substrate kinetics limitation of a process, it could at the same time make it thermodynamically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Tatsuoka et al ( 2008 ) and Ebrahimi et al ( 2011 ) could decrease H 2 accumulation in methanogenesis-inhibited ruminal batch cultures by adding fumarate or malate. Whilst the addition of a substrate or a fermentation intermediate might remove or decrease the substrate kinetics limitation of a process, it could at the same time make it thermodynamically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Through adding propionate formation intermediates, Tatsuoka et al (2008) and Ebrahimi et al (2011) had some success at decreasing H 2 accumulation in methanogenesis-inhibited ruminal batch incubations, which would indicate, that at least under their conditions, propionate formation was limited by thermodynamics or substrate kinetics (through the availability of a C skeleton). Fonty et al (2007) found that addition of fumarate to a methanogen-free ruminal incubation accelerated H 2 utilization without affecting its final point at 24 h, which would suggest a limitation of a substrate kinetic nature.…”
Section: Discussionmentioning
confidence: 99%
“…When methanogenesis was simultaneously inhibited with a chemical compound, increased availability of [H] not incorporated into CH 4 favored the conversion of the added carboxylic acids to the expected end products. In the presence of inhibitors of methanogenesis, the addition of propionate precursors malate (Mohammed et al, 2004) or fumarate (Tatsuoka et al, 2008;Ebrahimi et al, 2011) increased propionate production in vitro 1 Greater ranges in H 2 concentration in some studies in which methanogenesis was not inhibited are due to multiple measurements throughout the day in animals fed once or twice a day, rather than to variation caused by treatments imposed.…”
Section: The Competition For Dihydrogenmentioning
confidence: 99%